Mutation of mpv17 results in loss of iridophores due to mitochondrial dysfunction in tilapia - Xu, Jia; Li, Peng; Xu, Mengmeng; Wang, Chenxu; Kocher, Thomas D; Wang, Deshou (The Journal of heredity, 2025)
Mpv17 (mitochondrial inner membrane protein MPV17) deficiency causes severe mitochondrial DNA depletion syndrome in mammals and loss of pigmentation of iridophores and a significant decrease of melanophores in zebrafish. The reasons for this are still unclear. In this study, we established an mpv17 homozygous mutant line in Nile tilapia. The developing mutants are transparent due to the loss of iridophores and aggregation of pigment granules in the melanophores and disappearance of the vertical pigment bars on the side of the fish. Transcriptome analysis using the skin of fish at 30 dpf (days post fertilization) revealed that the genes related to purine (especially pnp4a) and melanin synthesis were significantly downregulated. However, administration of guanine diets failed to rescue the phenotype of the mutants. In addition, no obvious apoptosis signals were observed in the iris of the mutants by TUNEL staining. Significant downregulation of genes related to iridophore differentiation was detected by qPCR. Insufficient ATP, as revealed by ATP assay, α-MSH treatment, and adcy5 mutational analysis, might account for the defects of melanophores in mpv17 mutants. Several tissues displayed less mtDNA and decreased ATP levels. Taken together, these results indicated that mutation of mpv17 led to mitochondrial dTMP deficiency, followed by impaired mtDNA content and mitochondrial function, which in turn, led to loss of iridophores and a transparent body color in tilapia.